1991
DOI: 10.1042/bj2800277
|View full text |Cite
|
Sign up to set email alerts
|

pH-dependency of basic ligand binding to α1-acid glycoprotein (orosomucoid)

Abstract: The binding interactions of a series of basic ligands with alpha 1-acid glycoprotein (AAG) were examined as a function of pH. The binding to AAG increased with increasing pH, and the binding data were satisfactorily fitted to a model that incorporates the effect of pH and discriminates the association constants of neutral (non-protonated) and protonated forms of ligands. It was shown that ligands in the neutral form have a markedly higher affinity for AAG than the protonated forms, resulting in a concomitant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 9 publications
0
21
1
Order By: Relevance
“…A third explanation lies in the potentially different binding modalities of LAs and those drug classes examined by Kaliszan et al (1995), principally antihistamines and class II antiarrythmics. The model of Kaliszan et al (1995) is also inconsistent with a report on the binding of unfractionated AGP to six amphipathic amines: two antihypertensives, two antidepressants, an antipsychotic, and a coronary vasodilator (Urien et al, 1991). The neutral forms of these drugs bound to AGP more tightly than did their protonated counterparts by factors of 5 to 20.…”
Section: Downloaded Fromcontrasting
confidence: 52%
“…A third explanation lies in the potentially different binding modalities of LAs and those drug classes examined by Kaliszan et al (1995), principally antihistamines and class II antiarrythmics. The model of Kaliszan et al (1995) is also inconsistent with a report on the binding of unfractionated AGP to six amphipathic amines: two antihypertensives, two antidepressants, an antipsychotic, and a coronary vasodilator (Urien et al, 1991). The neutral forms of these drugs bound to AGP more tightly than did their protonated counterparts by factors of 5 to 20.…”
Section: Downloaded Fromcontrasting
confidence: 52%
“…Both proteins have only three His residues with a protein length of 201 amino acids. Also, 40% of these proteins contain carbohy- drates [26] which might mask the His groups, and that could explain why these proteins were not retained on the IMAC columns but were retained by the RP column. The protein apolipoprotein A-II does not have any His group on its surface to have retention on the IDA-metal columns.…”
Section: Highlights Of the Retention Of Some Typical Proteins On The mentioning
confidence: 97%
“…16,19,26 A study of the pH dependency of several basic drugs to AGP found that the drugs in the neutral form have a markedly higher affinity for AGP than the protonated forms, which suggests that hydrophobic interactions dominate high-affinity binding to AGP. 27 Recently, a thermodynamic study found that the entropic drive to AGP binding increases with decreasing global polarity of drugs, whereas the enthalpic drive increases with increasing polarity. 28 Here, we may expect that the protein domain is responsible for stereoselectivity.…”
mentioning
confidence: 99%